2017
DOI: 10.1093/abbs/gmx025
|View full text |Cite
|
Sign up to set email alerts
|

8-Bromo-7-methoxychrysin-blocked STAT3/Twist axis inhibits the stemness of cancer stem cell-like cell originated from SMMC-7721 cells

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a member of the family of latent cytoplasmic transcriptional factors that could regulate cell proliferation, survival, and development. It has been reported that Twist is a target gene of STAT3, and STAT3/Twist signaling plays an important role in regulating cancer progress. Here, to explore whether 8-bromo-7-methoxychrysin (BrMC) inhibits liver cancer stem-like cell (LCSLC) properties via disrupting STAT3/Twist signaling, we cultured SMMC-7721 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…3 , 4 To date, it has been confirmed that epithelial-mesenchymal transition (EMT), an embryonic developmental process, confers stem-cell like features to cancer cells. 5 , 6 Therefore, the development of agents targeting CSLCs to reverse EMT deserves further attention.…”
Section: Introductionmentioning
confidence: 99%
“…3 , 4 To date, it has been confirmed that epithelial-mesenchymal transition (EMT), an embryonic developmental process, confers stem-cell like features to cancer cells. 5 , 6 Therefore, the development of agents targeting CSLCs to reverse EMT deserves further attention.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally Lirdprapamongkol et al found that chrysin overcame TRAIL resistance of cancer cells mainly as blocking STAT3 25. Our recent study demonstrated that chrysin inhibited the sphere formation capability of SKOV3-derived ovarian cancer stem-like cells (CSLCs),26 and 8-Bromo-7-methoxychrysin, a synthetic analog of chrysin,27 reduced sphere-forming rate of the spheres originated from SMMC-7721 cells by blocking STAT3/Twist axis 28. However, the mechanisms underlying the regulation of STAT3 activation by chrysin are also unclear.…”
Section: Introductionmentioning
confidence: 80%
“…Previous study demonstrated that 8-Bromo-7-methoxychrysin could inhibit the stemness of CSLCs derived from SMMC-7721 cells by blocking the STAT3/Twist axis 28. Many studies have found that SHP-1 tumor suppression may result from its direct downregulating of p-STAT3 Tyr705.…”
Section: Resultsmentioning
confidence: 99%
“…The wound-healing assay was performed as previously described ( 35 ). Briefly, H460, A549 cells or their corresponding LCSLCs were seeded (2×10 5 cells/well) into a 6-well plate.…”
Section: Methodsmentioning
confidence: 99%